Growth of vertically aligned single-walled CNTs using alcohol catalytic CVD method - Mohd Abid, Mohd Asyadi Azam (AMREC SIRIM Malaysia, 2011)
A massive growth of vertically aligned single-walled carbon nanotubes (SWCNTs) from Al2O3-supported Co catalyst was performed using Alcohol Catalytic Chemical Vapor Deposition (ACCVD) method. Carpets of SWCNTs with an almost submillimeter height were grown on the Si/SiO2 substrates via this technique. Growth temperature dependence analysis had been carried out in the first place to elucidate parametric study in determining optimum growth conditions, in which the CVD time was fixed to t = 10 min and CVD reactor internal pressure at 3 kPa. The analysis confirmed the maximum height of SWCNTs films grown on the substrate to be TCVD = 750 o C. Structural properties of as-grown SWCNTs have been measured by Raman spectroscopy with various laser excitations where we confirmed a relatively high quality and pure SWCNTs: determined from Raman intensities, IG/ID ratio. Morphology observation of the very high SWCNTs yield was performed by Scanning Electron Microscope (SEM).